Penetapan Kawasan Perkotaan dan Batas Wilayah Perkotaan Berdasarkan Derajat Urbanisasi dan Kawasan Perkotaan Fungsional di Indonesia (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2026)
Urban boundary definitions are critical for service provision, spatial planning, and policy implementation; however, in Indonesia, urban delineation remains largely administrative and often fails to capture actual spatial and functional dynamics. This study aims to determine urban boundaries by integrating the degree of urbanization and functional urban area approaches using spatial population data and commuting patterns from the National Labor Force Survey (SAKERNAS). The degree of urbanization method classifies areas based on population density and settlement structure, while the functional urban area approach captures commuting-based interactions between urban cores and surrounding regions. Applied within a case study, the results reveal a mismatch between administrative boundaries and actual urban characteristics, where several areas exhibit strong urban traits despite lacking formal city status, and commuting patterns indicate that urban influence extends beyond administrative limits. These findings highlight the need for a more functional and data-driven approach to urban delineation to support more effective service provision and integrated planning across administrative boundaries.